Genetic and Non‐genetic Factors Associated With Constipation in Cancer Patients Receiving Opioids. Issue 6 (June 2015) - Laugsand, Eivor A; Skorpen, Frank; Kaasa, Stein; Sabatowski, Rainer; Strasser, Florian; Fayers, Peter; Klepstad, Pål
Abstract : OBJECTIVES: : To examine whether the inter‐individual variation in constipation among patients receiving opioids for cancer pain is associated with genetic or non‐genetic factors. METHODS: : Cancer patients receiving opioids were included from 17 centers in 11 European countries. Intensity of constipation was reported by 1, 568 patients on a four‐point categorical scale. Non‐genetic factors were included as covariates in stratified regression analyses on the association between constipation and 75 single‐nucleotide polymorphisms (SNPs) within 15 candidate genes related to opioid‐ or constipation‐signaling pathways ( HTR3E, HTR4, HTR2A, TPH1, ADRA2A, CHRM3, TACR1, CCKAR, KIT, ARRB2, GHRL, ABCB1, COMT, OPRM1, and OPRD1 ). RESULTS: : The non‐genetic factors significantly associated with constipation were type of laxative, mobility and place of care among patients receiving laxatives ( N =806), in addition to Karnofsky performance status and presence of metastases among patients not receiving laxatives ( N =762) ( P <0.01). Age, gender, body mass index, cancer diagnosis, time on opioids, opioid dose, and type of opioid did not contribute to the inter‐individual differences in constipation. Five SNPs, rs1800532 in TPH1, rs1799971 in OPRM1, rs4437575 in ABCB1, rs10802789 in CHRM3, and rs2020917 in COMT were associated with constipation ( P <0.01). Only rs2020917 in COMT passed the Benjamini–Hochberg criterion for a 10% false discovery rate. CONCLUSIONS: : Type of laxative, mobility, hospitalization, Karnofsky performance status, presence of metastases, and five SNPs within TPH1, OPRM1, ABCB1, CHRM3, and COMT may contribute to the variability in constipation among cancer patients treated with opioids. Knowledge of these factors may help to develop new therapies and to identify patients needing a more individualized approach to treatment.